Islam and ethnic tolerance: assessing Kyrgyz' Muslim religiosity and acceptance of Uzbeks in Kyrgyzstan. - Khamidov, Alisher; Nolle, David B. (Central Asian Survey, 2025)
Using a national opinion survey conducted in 2009 in Kyrgyzstan, we focused on responses from ethnic Kyrgyz respondents in the south where major riots between Kyrgyz and Uzbeks occurred in 1990 and 2010. We performed latent class analyses on these responses to assign Kyrgyz into Muslim religiosity categories and construct a social distance scale to measure Kyrgyz' levels of acceptance of Uzbeks living in Kyrgyzstan. We discovered that, in spite of ongoing unresolved interethnic grievances in the south, Kyrgyz who were members of the highly active Muslim religiosity category exhibited a significantly higher probability for accepting the closest relations (kin through marriage) with Uzbeks than Kyrgyz who were members of the non-religious category. Because other researchers indicated that religion did not play any role in causing the riots in 2010, we believe that Muslim religiosity could potentially play a role in developing beneficial relations between these ethnic groups.